Judicial Power, inclusive justice and intercultural justice - Malpartida Castillo, Víctor (2012)
The central aspect here is an account of how the Judiciary has gradually assumed an intercultural form of justice, ranging from the valuation of the anthropological appraisal to the organization of international congresses of intercultural justice, with constant concern for the relationship between ordinary justice and communal justice, ending with an Intercultural Coordination and Harmonization of Justice Bill in 2011